(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, we consider the stochastic Quantum Zakharov-Kuznetsov equation (SQZKE) perturbed in the Itô sense by multiplicative Brownian motion. We employ a suitable transformation for changing the SQZKE to another QZKE with random variable coefficients (QZKE-RVCs). Utilizing the modified extended tanh function method and the Jacobi elliptic function approach, we get novel hyperbolic, elliptic, trigonometric, and rational solutions for QZKE-RVCs. The SQZKE solutions can then be obtained. Additionally, we present many graphic representations to demonstrate how multiplicative Brownian motion affects the exact solutions of the SQZKE.